Renewable Energy Consumption, Climate Change, and Economic Growth: A Case of Selected Countries - Spetan, Khawlah Ali A.; AL- Rawabdeh, Mohammad M.; Al-Assaf , Ghazi I.; Al-Tal , Raad M. (Journal of Ecohumanism, 2024)
This research examines the nexus between renewable energy consumption, climate change, and economic growth across 88 countries, categorized by income levels (high, upper-middle, lower-middle, low, and Arab countries) from 1990-2020. Using the Panel Autoregressive Distributed Lag (PARDL) model, the study captures both short- and long-term relationships among the variables. Key findings reveal that economic growth is linked to rising temperatures, while the impact on precipitation varies across income groups. Non-renewable energy consumption has mixed effects: it mitigates climate change in developed countries but exacerbates pollution in developing nations. Conversely, renewable energy lowers average temperatures in lower-income countries, but in high-income countries, it shows positive correlations with climate change indicators. The significant error correction terms across all panels indicate a quick adjustment toward long-run equilibrium. The study underscores the need for tailored climate and energy strategies, advocating for increased renewable energy infrastructure in developing countries and improved energy efficiency in developed nations. For Arab countries, which face specific climate risks, enhanced regional cooperation on mitigation measures is recommended. This research emphasizes that addressing climate change requires strategies that consider the distinct economic and environmental contexts of different country groups.